The Influence of Transportation Support Capacity on The Development of Medan Johor District - Anitha Florida Ginting; Sirojuzilam Sirojuzilam; Agus Puwoko (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Roads are also referred to as a means of driving the region's economy because it can increase economic growth and reduce inequality between regions. Economic growth and the development of activity centers in Medan Johor led to an increase in population movement. Transportation as a movement supporting infrastructure has positive implications for the increasing growth and progress of the city, but it can also provide negative implications, such as congestion, irregularities and traffic accidents. The carrying capacity of transportation is a road as a means and transportation as infrastructure. Therefore, research is needed that aims to analyze the influence of transportation support capacity on the development of Medan Johor District. The research method is descriptive quantitative with survey approach. The research variables used are variable physical condition of the road, safety of road users, comfort of road users, speed of travel, smooth transportation, transportation capacity, effectiveness of transportation and development of the territory. The data was obtained from 100 respondents who live in Medan Johor through questionnaires. The data analysis method is done with multiple linear regression analysis. The results showed that the physical condition of the road, the comfort of road users, the speed of travel, the smoothness of transportation, transportation capacity, the effectiveness of transportation positively and siqnifikan to the development of the District of Medan Johor and the safety of road users positively and not siqnifikan to the development of the district of Medan Johor. It is necessary for the role of the Central Government and The Local Government of Medan city to continue to prioritize the development of transportation facilities and infrastructure, evaluate the development of land use, evaluate the granting of permits for the construction of shop houses and buildings that are used as business premises because it can result in increased vehicles, controlling the utilization of space in accordance with the General Plan of Spatial Planning of Medan City.